Deep sequencing of BCR heavy chain repertoires in myalgic encephalomyelitis/chronic fatigue syndrome - Ryback, Audrey A.; Cowan, Graeme J. M. (Frontiers in Immunology, 2025)
Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a common and debilitating chronic illness of unknown aetiology. Chronic infection and autoimmune responses have been proposed as two mechanisms that potentially underlie the pathogenesis of ME/CFS. To explore these disease hypotheses, we characterised the antigen-specific receptors of B cells using adaptive immune receptor repertoire sequencing. We compared the B-cell receptor (BCR) repertoires of 25 patients with mild/moderate ME/CFS, 36 patients with severe ME/CFS, 21 healthy controls, and 28 patients with multiple sclerosis (MS) to identify signatures of infection or autoimmune responses. ME/CFS patients did not display increased clonality or differential somatic hypermutation compared to healthy controls and patients with MS. One of two immunoglobulin heavy variable (IGHV) genes, IGHV3-30, reported to be increased in ME/CFS patients in a previous study, was replicated in patients with mild/moderate disease in our cohort. However, there was no evidence of ongoing adaptive responses in IGHV3-30 repertoires from mild/moderate ME/CFS patients with increased IGHV3-30 usage. There were no detectable repertoire signatures associated with infection or autoimmunity in repertoires from ME/CFS patients, but we observed skewing of the ratio of IgM to IgG BCRs in patients with mild/moderate ME/CFS, a preliminary finding that presents an opportunity for follow-up work.